Transition to a Green Economy: Government Policy in the Context of the Labor Market - Nuraliyeva, Rafiga; Zeynalov, Ali; Babayev, Mahammad; Gasimli, Murad (ADA University, 2025)
The global transition to the green economy requires adapting the labor market. The aim of the research is to identify strategies for the transition to a Green Economy in the context of Government Policy in the Labor Market. Although Azerbaijan has announced ensuring a high quality of environment and contribution to green energy as a national priority within the “Azerbaijan 2030: National Priorities for Socio-Economic Development” agenda, Azerbaijan faces challenges during the transition period. Main reasons are related to skill mismatch, lack of awareness, weak vocational trainings, dependency on oil and gas industry, limited institutional capacity, and insufficient labor market data. This study defines gaps in the current policies and offers alternative policies to fix these issues. Azerbaijan, as other developing nations, has challenges related to the transition process. Economic development and economic growth are different key words. Economic development contains more meaning than growth. Because of this, the transition process is more challenging. This research paper offers policies including green workforce creation policies, transition frameworks and regulations, Eco-Industrial Parks, tax incentives, and subsidies. However, the research paper is based on comparative analysis and benchmarks from Germany, United Kingdom, South Korea, Kazakhstan, Georgia, Netherlands, and so on. All policy options are evaluated based on efficiency, effectiveness, equity, feasibility, and flexibility. At the end, recommendations are provided for the government to ensure the transition to a green economy in Azerbaijan through practical, inclusive, and well-informed labor market policies that align with international best practices.
Keywords: Green economy -- Government policy.; Labor market -- Government policy.; Sustainable development -- Economic aspects.; Environmental policy -- Economic aspects.; Vocational education -- Environmental aspects.; Economic development -- Environmental aspects.